The THE EFFECTIVENESS OF INTERPROFESSIONAL COLLABORATION PRACTICE IN OPERATING ROOM - Mumtaz, Dzakiyatul Fahmi (Universitas Respati Yogyakarta, 2021)
Background: Interprofessional Collaboration Practice (IPCP) is a process when several different health care professionals provide comprehensive health services, working together with patients, patients' families, nurses (caregivers) and the community to provide excellent quality care. IPCP is a team-based care action that focuses on improving the quality of patient and family services but is still limited to being applied in hospitals, especially in the operating room. Aim: The purpose of this study was to determine the application of Interprofessional Collaboration Practice (IPCP) in the operating room. Method: This research is a descriptive analytic study with a systematic-literature review design. The databases used are Sciencedirect, Pubmed, Sage and Spingerlink using the search keywords â€œInterprofessional Collaboration Practice Implement* AND adult patient AND operat* room AND improved patient health statusâ€. Determination of scientific articles using the PRISMA Flow Diagram method by determining scientific articles according to research inclusion criteria. Result: The results of this literature review were reviewed in full and founded 4 articles on the effective application of IPCP in reducing the incidence of Surgical Site Infection (SSI) and stimulating an increase in the quality of care provided by the IPCP team to patients with a history of surgery. Conclusion: Interprofessional Collaboration Practice (IPCP) is effective in reducing Surgical Site Infection (SSI) and improving the quality of care for patients in operating room. Keyword: Interprofessional Collaboration Practice, IPCP, operating room, SSI